Indole Treatment Alleviates Intestinal Tissue Damage Induced by Chicken Coccidiosis Through Activation of the Aryl Hydrocarbon Receptor - Kim, Woo H.; Lillehoj, Hyun S.; Min, Wongi (Frontiers in Immunology, 2019)
Indoles, as the ligands of aryl hydrocarbon receptor (AhR), have been shown to possess immune-modulating property in terms of the balancing between regulatory T cells (Treg) and T helper 17 cells (Th17) activities. In the present study, we examined the effects of dietary indoles, 3,3’-diindolylmethane (DIM) and indole-3-carbinol (I3C), on CD4+T cell population and functions in chickens. Furthermore, the effects of dietary DIM treatment on chicken coccidiosis caused by an apicomplexan parasite were investigated. Dietary treatment of healthy chickens with DIM and I3C induced increased CD4+CD25+ (Treg) cells and the mRNA expression of IL-10, while decreasing number of CD4+IL-17A+ (Th17) cells and Th17-related cytokines transcripts expression in the intestine. In addition, we explored the role of AhR in indole-treated splenic lymphocytes by using AhR antagonist and our results suggested that DIM is a ligand for chicken AhR. In chicken coccidiosis, treatment of DIM increased the ratio of Treg/Th17 cells and significantly reduced intestinal lesion although no significant changes in body weight and fecal oocyst production were noted compared to non-treated control group. These results indicate that DIM is likely to affect the ratios of Treg/Th17 reducing the level of local inflammatory response induced by Eimeria or facilitate repairing process of inflamed gut following Eimeria infection. The results described herein are thus consistent with the concept that AhR ligand modulates the T cell immunity through the alteration of Treg/Th17 cells with Treg dominance. To our knowledge, present study is the first scientific report showing the effects of dietary indole on T cell immunity in poultry species.